2017
DOI: 10.1177/1559325817737932
|View full text |Cite
|
Sign up to set email alerts
|

Combination of β Adrenergic Receptor Block and Renin–Angiotensin System Inhibition Diminished the Angiotensin II-Induced Vasoconstriction and Increased Bradykinin-Induced Vasodilation in Hypertension

Abstract: In hypertension, the combination therapy is frequently used to obtain a better therapeutic effect and reduce adverse effects. One effective combination is with inhibitors and β-blockers of renin–angiotensin system. Although the mechanisms of action of each drug are already known, the antihypertensive mechanism is more complex and therefore the combined treatment mechanism is unclear. Specifically, the effect of the treatments of angiotensin-converting enzyme inhibitor or AT1 receptor antagonist with β-blocker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Our previous study reported that dietary intake of vitamins, especially B6, B9 and B12 and herb extracts such as agarwood significantly affect mood and stress and decrease inflammation through β2 adrenoreceptor (2rh1) binging energy [10]. Moreover, the combination of the betaadrenergic receptor block and renin-angiotensin system inhibition throughout diminished the Ang II-induced inflammatory cascade reaction and increased Ang (1-7) as well as its antiinflammatory effects [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study reported that dietary intake of vitamins, especially B6, B9 and B12 and herb extracts such as agarwood significantly affect mood and stress and decrease inflammation through β2 adrenoreceptor (2rh1) binging energy [10]. Moreover, the combination of the betaadrenergic receptor block and renin-angiotensin system inhibition throughout diminished the Ang II-induced inflammatory cascade reaction and increased Ang (1-7) as well as its antiinflammatory effects [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Results of the GC-MS analysis of the Pomegranate Seed Extract (PGSO) 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16. 17,1 Retention times (minutes); PA: peak area (%).…”
mentioning
confidence: 99%
“…Certainly, the mechanism underlying ACE-1 inhibition among different compounds, including peptides, is not expected to largely differ but rather the main targeted organ and pharmacokinetics will determine the clinical effect [24]. In line with previous studies [22,37], the prevention of bradykinin type 2 receptor desensitization and improvement of the circulating levels of bradykinin can be important for the sustained antihypertensive effect promoted by the regular consumption of hydrolysate in addition to ACE-1 inhibition. In light of current knowledge, the results open specific questions about the mechanisms underlying the antihypertensive effect of food-derived peptides, and with certainty show that the use of these peptides for developing antihypertensive functional foods for long-term use is feasible.…”
Section: Discussionmentioning
confidence: 76%
“…Catecholamine is an important humoral factor in the sympathetic adrenal myeloid system, which can cause constriction of peripheral blood vessels and increase diastolic pressure. The renin-angiotensin-aldosterone system also plays an important role in chronic stress by inducing increased angiotensin levels, regulating catecholamine secretion, and increasing blood pressure (102)(103)(104)(105). Sympathetic excitation is known to increase angiotensin II production by stimulating proximal cells and beta receptors in local tissues to promote renin secretion.…”
Section: Variation Of Hemodynamics and Blood Pressure Under Chronic Stressmentioning
confidence: 99%